TERBITNYA MODERNISME ISLAM: (Narasi Biografis Modernis Awal sebagai Inspirasi Organisasi Islam Modern di Indonesia) - Miswari Miswari (LPPM STAI Nida El-Adabi, 2023)
This article aims to explore the biographies of three early modernist figures in Indonesia, namely Cokroaminoto, Agus Salim, and Mohammad Natsir to find the typical roots of modern Islamic organizational movements in Indonesia. This research is a qualitative type with a biographical narrative approach. We explore references related to the biographies of these three figures to find the root of character for modern Islamic organizations in Indonesia. The research findings show that in Cokroaminoto's biographical narrative, it is found that the organizational control model requires administrative management skills, external relationship, and conflict management skills. Agus Salim's biographical narrative shows that he has pioneered the andragogy education system in the cadre of organizational members. Natsir's biographical narrative has shown the patron of the establishment of a modern Islamic school: by reducing the rote method, accommodating general education, and appreciating art education. Natsir can also be a reminder that intense involvement with the religious learning system can make an activist leave a formal education career opportunity as Natsir missed a scholarship opportunity to the Netherlands, because he was too impressed with the puritanical teachings of religion.